Euripides and the language of craft - Stieber, Mary C. (Mnemosyne, Supplements, 2011)
This first in-depth account of Euripides and the visual arts demonstrates how the tragedian used language to visual effect, whether through allusion or actual references to objects, motifs built around real or imaginary objects, or the use of technical terminology. The evidence presented in this study corroborates the concern for realism and the genre detail for which Euripides is parodied in Aristophanes' Frogs and presents him as a man of his time, like Socrates, fully versed in the ways and means of the visual arts as well as the verbal. In revealing the extent of the visual inclination of Euripides' language, this study reflects upon the larger dialogue between text and image, image and text.